Cytokeratin immunoreactivity of intestinal metaplasia at normal oesophagogastric junction indicates its aetiology. Issue 6 (1st December 2001) - Couvelard, A; Cauvin, J-M; Goldfain, D; Rotenberg, A; Robaszkiewicz, M; Fléjou, J-F
Abstract : BACKGROUND AND AIMS: Cytokeratin (CK) 7 and 20 patterns are specific for long and short segments of Barrett's oesophagus but their use has not been assessed in intestinal metaplasia arising in macroscopically normal gastro-oesophageal junction (GOJ). PATIENTS AND METHODS: This study was carried out in a large prospective series of 254 patients who underwent upper endoscopy, had normal gastro-oesophageal anatomy, and who had biopsies of the antrum, fundus, cardia, GOJ, and lower oesophagus. Intestinal metaplasia of the GOJ was typed by histochemistry with high iron diamine-alcian blue staining and by immunohistochemistry using CK7 and CK20 antibodies. Results were correlated with clinical, endoscopic, and pathological data. RESULTS: Sixty (23.6%) of our patients presenting with a normal GOJ had intestinal metaplasia. The CK7/CK20 pattern identified two groups of patients: one highly correlated with Barrett's and the other with characteristics of Helicobacter pylori gastritis. The Barrett's type CK7/CK20 pattern was related to a high frequency of gastro-oesophageal reflux symptoms (p<0.02) and normal endoscopic appearance of the stomach (p<0.03). In contrast, the gastric type CK7/CK20 pattern was linked to atrophic (p<0.02) or erythematous (p<0.05) appearance of the stomach (p<0.03), high frequency of H pylori infection (p<0.04), antral inflammation (p<0.006) with atrophy (p<0.02), and intestinal metaplasia (p<0.02). CONCLUSION: In patients presenting with intestinal metaplasia in normal appearing GOJ, the cytokeratin pattern identifies two groups of patients, one with features identical to those of long segment Barrett's oesophagus and one with features seen in H pylori gastritis. These data may be used by clinicians and should result in improved endoscopic surveillance strategies targeted specifically at patients at increased risk of Barrett's oesophagus and thus cancer.